English English - Puspita, Indah; Aldila, Herman (Dharma Pengabdian Perguruan Tinggi (DEPATI), 2023)
Kelurahan Lubuk Kelik is one of the new sub-districts which is the result of the expansion of Kelurahan Parit Padang in Province of Kepulauan Bangka Belitung, the majority of which is a post-tin mining area and conservation forest area. The issue of waste is the main environmental problem faced. Along the Lubuk Kelik road, which stretches for 12 km, there are at least 10-15 illegal waste dumping points located along the road in the oil palm plantation area and residents' land. The Various efforts to educate awareness of waste management was done but that does not cause environmental problems, including throwing rubbish in its place or making recycled crafts using plastic waste. The low direct impact felt sometimes makes this education less effective, especially as handicraft products based on recycled plastic waste are less popular with the market due to the lack of innovation and creativity. The training to empower PKK and housewives through the application of hydroponic technology using plastic bottle waste is expected to be an alternative solution to the household scale plastic bottle waste problem in the Kelurahan Lubuk Kelik. This activity is an effort to handle plastic bottle waste through a recycling use method based on community empowerment, especially housewives in terms of meeting their daily need for vegetables. This was chosen because vegetables are a basic need for society and are now quite expensive. Apart from that, hydroponic technology is more efficient than conventional vegetable plantations because it does not depend on soil fertility and land area and is free of pesticides. Apart from fulfilling daily needs, it is hoped that the community will be able to develop vegetables into superior commodities as additional income for the community.